Inhibition of Human Rhinovirus-Induced Cytokine Production by AG7088, a Human Rhinovirus 3C Protease Inhibitor - Zalman, L. S. (American Society for Microbiology, 2000)
Symptom severity in patients with human rhinovirus (HRV)-induced respiratory illness is associated with elevated levels of the inflammatory cytokines interleukin-6 (IL-6) and IL-8. AG7088 is a novel, irreversible inhibitor of the HRV 3C protease. In this study, AG7088 was tested for its antiviral activity and ability to inhibit the production of IL-6 and IL-8 in a human bronchial epithelial cell line, BEAS-2B. Infection of BEAS-2B cells with HRV 14 resulted in the production of both infectious virus and the cytokines IL-6 and IL-8. Treatment of HRV 14-infected cells with AG7088 resulted in a statistically significant (P, <0.05) dose-dependent reduction in the levels of infectious virus as well as IL-6 and IL-8 released into the cell supernatant compared to the results obtained for compound-free infected cells. AG7088 was also able to inhibit the replication of HRV 2 and 16 in BEAS-2B cells. In time-of-addition studies, AG7088 could be added as late as 14 to 26 h after HRV 14 infection of BEAS-2B cells and still result in a statistically significant (P, <0.05) reduction in the levels of infectious virus, IL-6, and IL-8 compared to the results obtained for compound-free infected cells. These findings have implications for the development of an antirhinovirus agent that may not only block virus replication but also diminish symptoms.